2018
DOI: 10.1057/s41599-018-0124-6
|View full text |Cite
|
Sign up to set email alerts
|

What makes people approve or condemn mind upload technology? Untangling the effects of sexual disgust, purity and science fiction familiarity

Abstract: The idea of separating a person's consciousness and transferring it to another medium-'mind upload'-is being actively discussed in science, philosophy, and science fiction. Mind upload technologies are currently also being developed by private companies in Silicon Valley, and similar technological developments have received significant funding in the EU. Mind upload has important existential and ethical implications, yet little is known about how ordinary people actually feel about it. The current paper aims t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
70
7
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(95 citation statements)
references
References 53 publications
11
70
7
1
Order By: Relevance
“…Our current set of studies offer new and timely insights into issues concerning automatized medical ethics, since, to our knowledge, vignette methodology has not previously been used to study personal autonomy violations involving autonomous AI agents. However, it is somewhat challenging to contrast our results with previous moral psychological work, since there are not that many papers focusing on the intersection of medical ethics and robotics, or more generally on the "moral psychology of robotics" (see Malle et al, 2015;Awad et al, 2018;Bigman & Gray, 2018;Bigman, Waytz, Alterovitz & Gray, 2019;Bonnefon et al, 2016;Laakasuo et al, 2018;Koverola et al, in press).…”
Section: Contextualizing the Resultsmentioning
confidence: 77%
“…Our current set of studies offer new and timely insights into issues concerning automatized medical ethics, since, to our knowledge, vignette methodology has not previously been used to study personal autonomy violations involving autonomous AI agents. However, it is somewhat challenging to contrast our results with previous moral psychological work, since there are not that many papers focusing on the intersection of medical ethics and robotics, or more generally on the "moral psychology of robotics" (see Malle et al, 2015;Awad et al, 2018;Bigman & Gray, 2018;Bigman, Waytz, Alterovitz & Gray, 2019;Bonnefon et al, 2016;Laakasuo et al, 2018;Koverola et al, in press).…”
Section: Contextualizing the Resultsmentioning
confidence: 77%
“…For example, patients and older adults preferred familiar social partners [26]. Furthermore, older adults might be unfamiliar with or even have negative feelings toward non-humanlike or mechanical robots due to their lower familiarity with new technology [27]. Therefore, older adults might prefer humanlike robots because, compared to non-humanlike robots, humanlike robots with higher familiarity could provide stronger emotional support for older adults.…”
Section: Discussionmentioning
confidence: 99%
“…Since we did not collect data of participants’ psychometric traits and experiences, such as anxiety traits and animal reminder sensitivity, we cannot be sure if the age differences in UVE observed in the current study resulted from differences in psychometric traits between age groups. Neither can we exclude other possible factors which might affect the UVE, including the relatively lower exposure of older adults to science fiction and their unfamiliarity with robots, which could be negatively correlated with the possibility of interacting with new technology [27].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, enhancement technologies may be seen primarily as violations of bodily purity, or as deviation from ingroup norms, which would make them a concern for those who prioritize binding values. Furthermore, previous research has shown that the individual levels of 'science fiction hobbyism' are associated with moral approval of mind upload technologies, even after controlling for the effects of moral foundations (Laakasuo et al, 2018). It therefore stands to reason that science fiction hobbyists could also hold more favorable attitudes toward brain implants.…”
Section: Non-human Superhumansmentioning
confidence: 98%
“…Schaich Borg et al, 2008;Haidt et al, 1997), and individual differences in disgust sensitivity are associated with self-placement on the liberal-conservative ideological continuum (Inbar et al, 2012). There is also evidence that sexual disgust specifically (see Tybur et al, 2009) predicts disapproval of transhumanist technologies like mind uploading (Laakasuo et al, 2018;Laakasuo et al, 2020). Why individual differences in disgust proneness would be associated with moral evaluations of situations that are not themselves disgust-evoking (see also Laakasuo et al, 2017) is still poorly understood; but such empirical connections may ultimately help develop a more cohesive theory of moral cognition.…”
Section: Non-human Superhumansmentioning
confidence: 99%